Language teaching via the internet: perception of english language teachers of higher learning institutions - Puteh, Marlia (Program Pengajian Diploma, 2002)
The Internet is gradually gaining its popularity in Malaysian higher institutions. Today, many language teachers spend endless and fruitless hours of information surfing via the Internet but their painstaking effort sometimes ended up with information that is completely different and irrelevant. However, there it is not much evidence on the application of the Internet in Malaysian higher institutions as well as teachers' view on their Internet application in language teaching. Therefore, the aim of this research is to seek the perception of Malaysian English language teachers of higher institutions on the use of Internet in language teaching and learning, particularly in English as a Second or Foreign Language. 15 respondents who are teaching in two universities were the subjects of the research. Their computing involvement, frequency of Internet navigation, and their opinions on their purposes of Web application were obtained. Results show that most of the teachers used the Internet in their language classes, allowed their students to communicate with them via e-mail, received the students' assignments via the technology and they also believed that the Internet is a valuable teaching tool in their language teaching.